2018
DOI: 10.1111/scs.12569
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the suffering assessment questionnaire in adults with chronic diseases or life‐threatening illness

Abstract: The results of confirmatory analysis indicated a good model fit that suggested that the advocated theoretical model is plausible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 18 publications
0
6
0
1
Order By: Relevance
“…Albanian (Roth & Ekblad, 2006), Croatian (Singer & Brähler, 2007), Brazilian (Bonanato et al, 2009), Hungarian (Biro et al, 2010), Korean (Han et al, 2007), Lingala (Bantu language spoken in parts of Africa) (Pham et al, 2010), Persian, Swahili (Rohani et al, 2010) as well as local languages in Africa Afar, Bilein, Hidareb, Kunama people, Nara, Saho, Tigre, and Tigrinya (Almedom et al, 2007;Getnet & Alem, 2019). An update per 2019 at least additional languages can be found: Portuguese (Encarnação et al, 2018) and Slovenia (Stern et al, 2019).…”
Section: The Validity and Reliability Of The Sense Of Coherencementioning
confidence: 99%
See 1 more Smart Citation
“…Albanian (Roth & Ekblad, 2006), Croatian (Singer & Brähler, 2007), Brazilian (Bonanato et al, 2009), Hungarian (Biro et al, 2010), Korean (Han et al, 2007), Lingala (Bantu language spoken in parts of Africa) (Pham et al, 2010), Persian, Swahili (Rohani et al, 2010) as well as local languages in Africa Afar, Bilein, Hidareb, Kunama people, Nara, Saho, Tigre, and Tigrinya (Almedom et al, 2007;Getnet & Alem, 2019). An update per 2019 at least additional languages can be found: Portuguese (Encarnação et al, 2018) and Slovenia (Stern et al, 2019).…”
Section: The Validity and Reliability Of The Sense Of Coherencementioning
confidence: 99%
“…More recent research shows three additional countries: Austria (Mautner et al, 2014), Estonia (Höjdahl et al, 2015), and Malaysia (Rostami et al, 2014). An update per 2019 shows further expansion: Ethiopia (Getnet & Alem, 2019), Ireland (Groarke et al, 2018), Portugal (Encarnação et al, 2018), and Slovenia (Stern et al, 2019).…”
Section: The Validity and Reliability Of The Sense Of Coherencementioning
confidence: 99%
“…A recent systematic review of measures specifically designed to assess the experience of suffering identified four instruments judged to be have adequate psychometric scale development (Gutiérrez-Sánchez et al, 2020): the Suffering Pictogram (Beng et al, 2017), the Mini-Suffering State Examination (MSSE) (Aminoff et al, 2004, the Pictorial Representation of Illness and Self-Measure (PRISM) (Büchi et al, 2002), and the Suffering Assessment Questionnaire in Adults with Chronic Diseases or Life-Threatening Illness (SAQ) (Encarnação et al, 2018). The reviewers concluded that, of these four, the Suffering Pictogram (Beng et al, 2017) was most the methodologically sound and most useful for application in palliative care.…”
Section: Resultsmentioning
confidence: 99%
“…Because of ease of administration, PRISM was identified in a 2015 systematic review (Best et al, 2015) as the most promising tool for measuring the burden of suffering caused by illness. The SAQ (Encarnação et al, 2018) Assesses four dimensions of suffering: intrapersonal and interpersonal suffering, awareness of suffering, and spiritual suffering 12-Item scale. Each item is rated on a 5-point scale ("totally agree" to "totally disagree").…”
Section: Measuring Sufferingmentioning
confidence: 99%
“…"If these fears remain unchecked, they can lead these students to unnecessary suffering" (Wright 2020, p. 188). When exploring the concept of suffering, literature is consistent in relating sadness, fear, anguish, distress, loss; pain and threat to the individuals' integrity as a manifestation of suffering (Cassell 2004;Delio 2020;Encarnação, Oliveira, & Martins 2018;Wright 2020). Fear can usually be experienced as an unpleasant emotion triggered by a constraining belief.…”
Section: Introductionmentioning
confidence: 99%